Performance of liquidâliquid hydrocyclone (LLHC) for treating produced water from surfactant flooding produced water - Ku Ishak, K.E.H. (Emerald Group Holdings Ltd., 2020)
Purpose: The purpose of this study is to investigate the performance of the fabricated liquidâliquid hydrocyclone (LLHC) with dimensions similar to those of one of the Malaysian oilfields with the presence of an anionic surfactant, S672. The effect of salinity and initial oil concentration were also investigated following the actual range concentration. Design/methodology/approach: The current control systemâs pressure drop ratio (PDR) does not necessarily lead to an efficient LLHC. Therefore, rather than using the PDR, the efficiency of the LLHC was analyzed by comparing the concentration of oil in the effluents with the concentration of oil at the feed of the LLHC. An LLHC test rig was developed at Centre of Enhanced Oil Recovery, Universiti Teknologi PETRONAS. Emulsions were prepared by mixing the brines, S672 and oil by using Ultra Turrax ultrasonic mixer. The emulsion was pumped into the LLHC at different feed flowrate and split ratio. The brines concentration, initial oil concentration and S672 concentration were also varied in this study. Samples were taken at the underflow of the LLHC and the oil in water concentration analysis was done for the samples using TD-500D equipment. Findings: It was found that the efficiency of oil removal decreased with an increase in S672 concentration but increased with the increase in salinity and initial oil concentration. Originality/value: The optimum feed flowrate for the LLHC of 45 mm diameter and length of 1,125 mm with the presence of S672 surfactant was found to be 40 L/min with a split ratio of 14. This study can be used as a guidance for future optimization of the LLHC in the presence of the surfactant. Â© 2019, Emerald Publishing Limited.